Influence of neutron irradiation on conduction cooling superconducting magnets. Issue 1 (November 2015) - Yang, Y; Yoshida, M; Ogitsu, T; Makida, Y; Nakamoto, T; Okamura, T; Sasaki, K; Sugano, M
Abstract: The conduction-cooled superconducting magnets are now widely used in various applications due to their minimum usage of helium. In the accelerator science, they also play an increasingly important role in particle detector solenoids because they can minimize the materials needed for the magnet such that they can be more transparent against irradiated particles. For the same reason they are currently used in high radiation environments because they can reduce the heat load from the irradiation. However, the hadronic reactions, such as neutron or proton irradiation, can create degradation on the thermal conductivity of pure aluminum which is used as a cooling path. It leads to a poor cooling condition of the magnets. In Japan, there are two conduction-cooled superconducting magnets for muon production; one is already constructed and under operation, the other is now under construction. This paper briefly reports the influence of the irradiation on those magnets and discusses the possibilities of HTS based conduction-cooled magnets under high irradiation environments.